New Trend in Hop Breeding at the Hop Research Center Huell - Lutz, anton; Kammhuber, Klaus; Seigner, Elisabeth (BrewingScience, 2012)
Hop cultivars have been developed at the Hop Research Center Huell since 1926. Until recently, all breeding programmes pursued the objectives to develop aroma varieties of the classical European noble aroma type and high yielding, high-alpha varieties. Both groups fully satisfied the demands of growers and brewers worldwide. However, initiated by the US craft brewers and also taken up by other creative brewers worldwide novel hop-derived aroma and flavour notes in beer attracted much attention. Therefore, new breeding efforts started in 2006 which already brought forth several experimental lines which impart multifaceted floral, fruity and citrusy aroma impressions to beer. Two hop varieties introducing mandarin-orange or fruity-piney notes to beer have already been submitted for registration for Plant Variety Rights and others will follow.